Evaluation of a semi-automated platelet-counting system. Issue 4 (April 1977) - Rowan, R M; Fraser, C; Gray, J H; McDonald, G A
Abstract : Coulter Electronics Ltd have produced a semi-automated platelet-counting system. Platelet-rich plasma may be obtained either by tube sedimentation or by means of the Thrombo-fuge, the latter being an instrument designed to produce accelerated sedimentation. The instrument is linear over the entire range of platelet counts, and machine reproducibility is good. Comparison of machine-rated with visual counts satisfied statistical evaluation. The technique can be handled by one operator and platelet counts can be achieved at the rate of 30 per hour by both methods although individual counts on the Thrombo-fuge may be obtained in approximately one-quarter of the time required for tube sedimentation. The throughput using the Thrombo-fuge could certainly be doubled were two sample plates supplied. Few problems were encountered during the evaluation and most could be avoided by meticulous technique. Visual counts must be performed when the sample haematocrit is greater than 50%-Discrepant counts have been obtained in patients with white cell counts exceeding 50 X 10(9)/1 and in patients with giant platelets. ESR elevation for any reason does not lead to serious discrepancy in results. The incidence of platelet clumping due to the presence of platelet agglutinins and of microclot formation due to inadequate mixing is probably much higher than is commonly thought, and certainly peripheral blood film scrutiny should never be omitted in patients with low counts. Careful examination of peripheral blood films must be combined with instrument counting for some time lest further causes of discrepant counting emerge.